A case study of oxytocin massage intervention for breastfeeding problems Ineffective in post-cesarean section patients - Sumarni Sumarni; Yuni Purwati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Breast milk is the best food for babies because it contains complete nutrition, enzymes, hormones, and antibodies that play a role in improving the immune system and supporting optimal growth of babies. Exclusive breastfeeding for the first 6 months of life is an important effort in reducing infant morbidity and mortality. However, in practice, many mothers still experience obstacles in breastfeeding, especially in the early postpartum period. Purpose: to determine the effectiveness of oxytocin massage in increasing breast milk production in postpartum patients with cesarean section. Method: Data collection methods were carried out through interviews, observations, and interventions, with assessment indicators using pretest and posttest evaluations, namely measuring the respondent's condition before and after the intervention was given. This study was conducted on June 9, 2025, in the Sakina Ward of PKU Muhammadiyah Hospital, Yogyakarta. Results: The results of the case study showed that after two 10-15 minute oxytocin massage interventions, breast milk production increased, and mothers felt more relaxed and comfortable Conclusion: This study is expected to be one of the interventions that midwives and nurses can implement for postpartum mothers to help increase breast milk production and support the success of exclusive breastfeeding